KONSEKUENSI PENERIMAAN OPINI GOING CONCERN DAN KUALITAS AUDITOR TERHADAP COST OF DEBT - Evi Grediani; Nanik Niandari (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2017)
This paper described empirical research examining the effect of auditor going concern opinion and auditor quality on cost of debt. Auditor going concern opinion is measured by dummy variable, which value of 1 if the opinion is going concern, and 0 otherwise. Auditor quality is also measured by dummy variable, which value 1 if the opinion given by Big-4 auditor, and 0 otherwise. Cost of debt is measured by interest expense divided by total debt. Using multiple regression analysis and a sample of 244 manufacturing company periods 2011 – 2014, the research find that auditor quality negatively effect the cost of debt and auditor going concern opinion doesn’t effect cost of debt.